The relationship between socio-economic statuses to nutritional status of first grade students in private primary school in north Surabaya - M Gita Jayanata, -
Abstract: Introduction: Low socio-economic status is one of the major causes of malnutrition. However, several studies of students at private elementary schools, which are often considered to have a good socio-economic status, show that malnutrition (both under and overnutrition) is quite high as measured based on BAZ (BMI-for-aged-Z-score) indicator. Method: This cross-sectional design study began in March 2020 and finish in November 2021 by collecting data from the Google form questionnaire. As many as 86 students in first-grade students who were in two private elementary schools, SD Al-Irsyad and SD Al-Muttaqien in North Surabaya became the sample (total sampling). The independent variable was the student’s socio-economic and the dependent variable was the student’s nutritional status based on the BAZ indicators. The wilcoxon test was used to determine the relationship between socio-economic status and nutritional status of students. Results: The most common student characteristics come from aged 7 years old (70%), boy (64%), and SD Al-Irsyad (53,5%). The highest nutritonal status are normal (57.0%), followed by overnutrition (12,8%-overweight and 20.9%-obese) and undernutrition (9,3%-thin). Based on family socio-economic status, most of them have upper education level (62.8%-fathers and 66.3%-mothers), working status (97.7%-fathers and 52.3%-mothers), and upper family expenditure level (60.5%). However, there is no relationship between socio-economic status and nutritional status of students (p > 0.05). Conclusion: The results of this study prove that there is no relationship between socio-economic status and nutritional status of students because the data from the two variables are less varied. More varied data are needed in further research.